Spodoptera exigua modulates gossypol biosynthesis in cotton Gossypium hirsutum. Issue 1 (1st January 2017) - Zebelo, Simon; Disi, Joseph; Balusu, Rammohan; Reeves, Benjamin; Fadamiro, Henry
ABSTRACT: Cotton plants induce high levels of gossypol in response to herbivore damage. However, little is known about the mechanisms by which insect herbivory modulates gossypol biosynthesis in cotton plants. Here, we report the mechanism by which herbivore damage or insect-originated elicitors modulate the biosynthesis of gossypol and jasmonic acid (JA) in plants. Spodoptera exigua larval-damaged (HD) cotton plants and mechanically damaged plants treated with S. exigua oral secretion (MDOS) showed higher levels of gossypol and JA as well as increased transcript levels of genes involved in the biosynthesis of both secondary plant metabolites, compared to undamaged (UD) or mechanically damaged (MD) plants. In correlation with the observed induction of gossypol and JA, S. exigua larvae that fed on HD and MDOS cotton plants showed significantly reduced weight. The findings provide a better insight into the molecular mechanisms mediating herbivore-induced plant defense.